(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study examines the transformation of adaptive leadership in facing educational disruption in the digital era. The digital era has fundamentally changed the educational landscape, requiring educational leaders to adapt quickly to changes in technology, pedagogy, and stakeholder expectations. The purpose of this study is to analyze the characteristics and strategies of effective adaptive leadership in responding to the challenges of digital disruption in educational institutions. The research method uses a descriptive qualitative approach with a Systematic Literature Review (SLR) model of journal articles, books, and relevant scientific publications from various academic databases for the period 2020-2025. The results show that adaptive leadership in the digital era is characterized by the ability to identify technological opportunities, flexibility in decision-making, empowerment of learning communities, and openness to innovation. Adaptive leaders are able to facilitate digital transformation by building a collaborative culture, developing digital literacy, and creating a learning ecosystem that is responsive to change. The findings also reveal the importance of balancing technology adoption and maintaining humanistic educational values. This study provides theoretical contributions regarding contemporary leadership models and practical implications for the development of educational leadership competencies in facing the challenges of the ever-evolving digital era.